On the type species of Geophilus Gistel, 1834 (Coleoptera: Scarabaeidae: Aphodiinae) - Nardi, Gianluca; Dellacasa, Giovanni; Dellacasa, Marco (Zootaxa, 2018)
Geophilus Gistel, 1834 (Insecta: Coleoptera: Scarabaeidae: Aphodiinae) is invalid being a junior homonym of Geophilus Leach, 1814 (Myriapoda: Chilopoda: Geophilomorpha: Geophilidae) and of Geophilus Schönherr, 1823 (Insecta: Coleoptera: Curculionidae). Scarabaeus asper Fabricius, 1775 was recently designated as type species of Geophilus Gistel, 1834, making Geophilus a junior synonym of Psammodius Fallén, 1807 (Insecta: Coleoptera: Scarabaeidae: Aphodiinae: Psammodiini: Psammodiina). However, there is clear evidence that Scarabaeus asper Fabricius, 1775 sensu Gistel, 1834 is Ptinus germanus Linnaeus, 1767, currently Rhyssemus germanus (Linnaeus, 1767) (Insecta: Coleoptera: Scarabaeidae: Aphodiinae: Psammodiini: Rhyssemina). To resolve this issue, the type species of Geophilus Gistel, 1834 is here fixed (under Article 70.3.2 of the International Code of Zoological Nomenclature) as Ptinus germanus Linnaeus, 1767, misidentified as Scarabaeus asper Fabricius, 1775 in the original paper. Scarabaeus asper Fabricius, 1775 sensu Mulsant, 1842 (= Ptinus germanus Linnaeus, 1767) is the type species of Rhyssemus Mulsant, 1842, therefore Rhyssemus Mulsant, 1842 is a junior synonym of Geophilus Gistel, 1834 (new synonymy). Although it has priority, Geophilus Gistel, 1834 is a junior homonym and therefore invalid, so Rhyssemus Mulsant, 1842 remains the valid name of this taxon.